Efektifitas Penggunaan Manitoba Trap dalam Surveilans penyakit Bersumber Lalat di Kabupaten Tanah Bumbu, Kalimantan Selatan - Dicky Andiarsa; Dian Eka Setyaningtyas; Ika Setianingsih; Abdullah Fadilly; Syarif Hidayat; Budi Hairani (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2016)
Flies-vector control programs are essential to prevent flies-borne diseases. These activities consist of surveillance to determine the multiplication and distribution patterns of flies, as well as efforts to control flies populations. Flies trap as a surveillance tool was vary according to the interests of the user. Manitoba trap and bottled trap have been widely used to control flies population. This study aimed to determine the effectiveness of both traps type and their modification form for the benefit of the survey, thus it can be a recommendation for flies surveillance program manager. This was a quasi-experimental study design conducted on January 2016 in twocattle farm in Kersik Putih and Segumbang Village, Tanah Bumbu District, South Kalimantan. There were 4 types of trap used in this study: 1) Manitoba trap with black cloth; 2) Manitoba trap with domestic waste or animal excreta as bait; 3) Bottled trap filled with sugar and vinegar solution; and 4) Bottled trap with domestic waste or food scraps. Each type of trap was doubled.Traps was put in pre-randomized spot around cattle cage and leftfor 4 days. The number of flies trapped ranged between 0-55, with Stomoxys calcitrans and Musca Linnaeus as the most species found trapped. Manitoba trap with domestic waste or animal excreta has the highest mean of density compared to the other three trap types. This study showed that Manitoba trap is fairly effective to be used as a surveillance tool in the open area offarm.